Β-Cyclodextrin Production by Cyclodextrin Glucanotransferase from an Alkaliphile Microbacterium terrae KNR 9 Using Different Starch Substrates. (25th August 2016) - Rajput, Kiransinh N.; Patel, Kamlesh C.; Trivedi, Ujjval B.
Abstract : Cyclodextrin glucanotransferase (CGTase, EC 2.4.1.19) is an important member of α -amylase family which can degrade the starch and produce cyclodextrins (CDs) as a result of intramolecular transglycosylation (cyclization). β -Cyclodextrin production was carried out using the purified CGTase enzyme from an alkaliphile Microbacterium terrae KNR 9 with different starches in raw as well as gelatinized form. Cyclodextrin production was confirmed using thin layer chromatography. Six different starch substrates, namely, soluble starch, potato starch, sago starch, corn starch, corn flour, and rice flour, were tested for CD production. Raw potato starch granules were found to be the best substrate giving 13.46 gm/L of cyclodextrins after 1 h of incubation at 60°C. Raw sago starch gave 12.96 gm/L of cyclodextrins as the second best substrate. To achieve the maximum cyclodextrin production, statistical optimization using Central Composite Design (CCD) was carried out with three parameters, namely, potato starch concentration, CGTase enzyme concentration, and incubation temperature. Cyclodextrin production of 28.22 (gm/L) was achieved with the optimized parameters suggested by the model which are CGTase 4.8 U/L, starch 150 gm/L, and temperature 55.6°C. The suggested optimized conditions showed about 15% increase in β -cyclodextrin production (28.22 gm/L) at 55.6°C as compared to 24.48 gm/L at 60°C. The degradation of raw potato starch granules by purified CGTase was also confirmed by microscopic observations.